2018
DOI: 10.1161/strokeaha.118.022279
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Paired With Upper Limb Rehabilitation After Chronic Stroke

Abstract: safety, feasibility, and efficacy of VNS paired with upper limb rehabilitation in chronic ischemic stroke, with blinded, sham VNS control. Methods This article adheres to the American Heart Association Journals' implementation of the Transparency and Openness Promotion Guidelines. Requests for data will be considered by the corresponding author after Food and Drug Administration postmarket approval. This was a randomized, sham stimulation controlled, and fully blinded study of VNS paired with rehabilitation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
194
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(223 citation statements)
references
References 7 publications
5
194
0
2
Order By: Relevance
“…The Food and Drug Administration (FDA) approved vagus nerve stimulation (VNS) in 1997 as an adjunctive therapy in adults with partial onset epilepsy refractory to medications (Morris et al 2013) (FDA, 1997). Subsequently, VNS was FDA approved for the treatment of depression (Wheless, Gienapp, and Ryvlin 2018), and is in clinical trials for diverse conditions such as hypertension (Ng et al 2016), heart failure (De Ferrari et al 2017), rheumatoid arthritis (Koopman et al 2016), tinnitus (Tyler et al 2017) and stroke rehabilitation (Kimberley et al 2018). Despite the growing clinical interest and some remarkable success in individual patients, VNS therapeutic effects are variable from patient to patient and are often limited by side effects including cough, throat pain, voice alteration and dyspnea (De Ferrari et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Food and Drug Administration (FDA) approved vagus nerve stimulation (VNS) in 1997 as an adjunctive therapy in adults with partial onset epilepsy refractory to medications (Morris et al 2013) (FDA, 1997). Subsequently, VNS was FDA approved for the treatment of depression (Wheless, Gienapp, and Ryvlin 2018), and is in clinical trials for diverse conditions such as hypertension (Ng et al 2016), heart failure (De Ferrari et al 2017), rheumatoid arthritis (Koopman et al 2016), tinnitus (Tyler et al 2017) and stroke rehabilitation (Kimberley et al 2018). Despite the growing clinical interest and some remarkable success in individual patients, VNS therapeutic effects are variable from patient to patient and are often limited by side effects including cough, throat pain, voice alteration and dyspnea (De Ferrari et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its approved use in treatment-resistant epilepsy [1] and depression [2], vagus nerve stimulation (VNS) may provide new treatment options for a wide range of illnesses. Long-term VNS is currently being explored in the treatment of brain disorders, such as tinnitus [3,4], stroke [5,6], and Alzheimer's disease [7,8], as well as peripheral organ and systemic diseases, including heart failure [9], cardiac arrhythmias [10][11][12][13], pulmonary hypertension [14,15], rheumatoid arthritis [16], Crohn's disease [17], and lupus [18]. The relatively recent discovery that the VN modulates the inflammatory response [19][20][21][22] might broaden the range of future indications for VNS, as inflammation is implicated in many common chronic diseases, such as type 2 diabetes, obesity, and atherosclerosis [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on VNS/taVNS stimulation have only reported improvement of the upper limb in poststroke patients, and they have not analyzed the effects on flexor or extensor synergy [7,8]. Our study makes an important contribution in this regard, as our results demonstrate improvement in both flexor and extensor synergy with AIA.…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 56%
“…e brainstem, as a supraspinal center, plays an important role in maintaining posture and voluntary movement. Recently, emerging evidence indicated vagus nerve stimulation as well contributed to the increase of Fugl-Meyer assessment (FMA) on the upper limb after stroke [7,8]. Transcutaneous auricular branch vagus nerve stimulation (taVNS), a noninvasive alternative therapy, has similar benefits to invasive vagus nerve stimulation in terms of enhancing the effects of physiotherapy for upper limb motor recovery after stroke [7].…”
Section: Introductionmentioning
confidence: 99%